Re-evaluating the risk costing agenda in PPP projects - Almarri, Khalid (2020)
Purpose The level at which risk is priced and the magnitude of risks transferred to the private sector will have a significant impact on the cost of the public–private partnership (PPP) deals as well as on the value for money analysis and on the section of the optimum investment options. The price of risk associated with PPP schemes is complex, dynamic and continuous throughout the concession agreement. Risk allocation needs to be re-evaluated to ensure the optimum outcome of the PPP contract. Design/methodology/approach This paper provides a coherent theoretical framework for dealing with scenarios of potential gain and loss from retaining or transferring risks. Findings The outcome indicates that using the proposed framework will provide innovative ways of deriving risk prices in PPP projects using several risk determinants strategies. Practical implications In costing risks, analysts have to take into consideration the balance between the cost of risk transfer and the cost of losses if risk is retained. Originality/value This paper contributes to the PPP literature and practice by proposing a framework which is consistent with a risk allocation approach in PPP projects, where the key proposition is that risk pricing can overload project debt leading to loss of value.